Tunisian and Guinean Support for the Algerian Cause through Border Movements and International Conferences - Samira, Negadi (Journal of Ecohumanism, 2025)
The mechanisms of continental affiliation and the African dimension present during the Algerian liberation revolution brought with them support from a number of African countries. Among these were Tunisia and Guinea. Each of these nations offered distinct African assistance that strengthened the Algerian cause, both in its armed struggle and in its political advocacy at international conferences. This support was evident in the border movements between Tunisia, Algeria, and Guinea, and in the organization of conferences that aimed to promote the Algerian issue, grant it international visibility, and secure African and global backing. This also involved highlighting the revolutionary efforts of Algerian heroes and citizens. From this context arises the central research question: What was the nature of the Tunisian and Guinean support for the Algerian cause? Did this support succeed in raising international awareness about the Algerian issue? Was the support material, moral, or both? To address this problem, it is necessary to define the broader framework of Tunisian and Guinean support in the face of global public opinion, especially through the United Nations. It is also essential to examine the regional and continental dimensions of this support.